New Four-Channel Resonant Boost DC/DC Converter - Janos Hamar; Peter Stumpf (IEEE Access, 2021)
Multichannel resonant DC/DC converters have recently been popular in diverse fields, where multiple output voltage levels are required, such as supplying multilevel inverters. This paper is devoted to present the new member of a four-channel resonant DC/DC converter family, having consisted till now of step down as well as step-up/down configurations. The new converter is capable of realizing the power flow amongst the two input and the four output channels in order to maintain the required equal or unequal output voltages. In the meanwhile, it offers the benefits of soft-switching capability, including zero voltage (ZVS) and zero current switching (ZCS), resulting in high efficiency and reduced electromagnetic interference (EMI). The presentation of the new boost converter topology is followed by a detailed steady-state analysis. The focus is on the symmetrical operation of the converter in discontinuous current conduction mode (DCM). Possible sets of control variables are revealed and their effect on the operation, especially on the output voltages and powers is analyzed in detail. A step-by-step calculation procedure is also proposed to determine the circuit parameters. The outcomes of simulations and experiments validate the theoretical results.